The bride wore pearls [large type] - Carlyle, Liz (Avon romance., 2012)
Beneath the elegant facade of Victorian high society, the mysterious men of the St. James Society play only by rules of danger and desire. Rance Welham, the Earl of Lazonby, has survived scandal and disgrace, even evading the Queenu2019s justice at the end of a hangmanu2019s rope. Now heu2019s about to gamble everything on something far more dangerousu2014desire. An exotic and elegant beauty, Lady Anisha Stafford fled her native India to seek refuge within Londonu2019s secretive St. James Society. But accepting protection from someone called a cold-hearted killer is a double-edged sword, especially when heu2019s the most intriguing man Anisha has ever laid eyes upon. In a world where treachery abounds, no one can be trusted, and no true passion can be denied. Together, these two tempestuous souls will risk their lives for a love that could redeem them or destroy everything they hold dear.